Extracellular vesicles derived from tumour cells as a trigger of energy crisis in the skeletal muscle. Issue 1 (20th December 2021) - Pin, Fabrizio; Beltrà, Marc; Garcia‐Castillo, Lorena; Pardini, Barbara; Birolo, Giovanni; Matullo, Giuseppe; Penna, Fabio; Guttridge, Denis; Costelli, Paola
Abstract: Background: Cachexia, a syndrome frequently occurring in cancer patients, is characterized by muscle wasting, altered energy and protein metabolism and impaired myogenesis. Tumour‐derived microvesicles (TMVs) containing proteins, messenger RNAs (mRNAs), and non‐coding RNAs could contribute to cancer‐induced muscle wasting. Methods: Differential ultracentrifugation was used to isolate TMVs from the conditioned medium of Lewis lung carcinoma and C26 colon carcinoma cell cultures. TMVs were added to the culture medium of C2C12 myoblasts and myotubes for 24–48–72 h, and the effects on protein and energy metabolism were assessed. TMVs were also isolated from the blood of C26‐bearing mice. MicroRNA (miR) profile of TMVs was obtained by RNA‐seq and validated by digital drop PCR. Selected miRs were overexpressed in C2C12 myoblasts to assess the effects on myogenic differentiation. Results: Differentiation was delayed in C2C12 myoblasts exposed to TMVs, according to reduced expression of myosin heavy chain (MyHC; about 62% of controls at Day 4) and myogenin (about 68% of controls at Day 4). As for myotubes, TMVs did not affect the expression of MyHC, while revealed able to modulate mitochondria and oxidative metabolism. Indeed, reduced mRNA levels of PGC‐1α (C = 1 ± 0.2, TMV = 0.57 ± 0.06, normalized fold change, P  < 0.05) and Cytochrome C (C = 1 ± 0.2, TMV = 0.65 ± 0.04, normalized fold change, P  < 0.05), associated with increased BNIP3 expression (C = 1 ± 0.1, TMV = 1.29 ± 0.2, normalized fold change, P  < 0.05), were observed, suggesting reduced mitochondrial biogenesis/amount and enhanced mitophagy. These changes were paralleled by decreased oxygen consumption (C = 686.9 ± 44 pmol/min, TMV = 552.25 ± 24 pmol/min, P  < 0.01) and increased lactate levels (C = 0.0063 ± 0.00045 nmol/μL, TMV = 0.0094 ± 0.00087 nmol/μL, P  < 0.01). A total of 118 miRs were found in MVs derived from the plasma of the C26 hosts; however, only three of them were down‐regulated (RNA‐seq): miR‐181a‐5p (−1.46 fold change), miR‐375‐3p (−2.52 fold change), and miR‐455‐5p (−3.87 fold change). No correlation could be observed among miRs in the MVs obtained from the blood of the C26 host and those released by C26 cells in the culture medium. Overexpression of miR‐148a‐3p and miR‐181a‐5p in C2C12 myoblasts revealed the ability to impinge on the mRNA levels of Myf5, Myog, and MyHC ( Myh4 and Myh7 ). Conclusions: These results show that in C2C12 cultures, TMVs are able to affect both differentiation and the mitochondrial system. Such effects could be related to TMV‐contained miRs.